Sailing Toward Stress: How Compliance Demands Influence Seafarers’ Wellbeing - Ausan, Dec Airo Mari (Nama Jurnal Akmi, 2025)
Purpose - This study examines how preparation for strict Port State Control Inspections (PSCI) by the Australian Maritime Safety Authority (AMSA), influences the welfare, living and working conditions of seafarers on board PSC vessels in New South Wales. It examines how the onus of ensuring regulatory compliance for ships – particularly in terms of safety, the environment, and labor – impacts the physical, mental, and emotional well-being of seafarers. Some elements of seafarers’ welfare were examined, revealing that compliance with work/rest hours, food quality, accommodation, leadership practices, and the length of the voyage are determining factors. Methodology – A quantitative, cross-sectional research design was employed to gather information from 300 seafarers across various ranks and vessel classes. Data revealed strong demand for improvements in leadership, standardization of living conditions, management of fatigue, and regard for seafarers’ physical well-being. Findings – The findings show extensive differences in welfare between ranks, with senior (management and operational) staff reporting higher levels of fatigue, stress and dissatisfaction than support personnel. A last-minute rush of too little food, improper accommodation and disrupted work/rest hours in expectation of an imminent inspection heightened stress and fatigue. Originality –.These findings suggest that allowing sufficient time to carry out inspections and attending to the welfare of seafarers can significantly reduce stress levels, which, in turn, improves the morale of the entire crew, leading to safer.